2019
DOI: 10.3390/app9061099
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Freezing and Melting Characteristics of Graphene-Based Phase Change Nanocomposite for Cold Thermal Energy Storage Applications

Abstract: In the present work, the freezing and melting characteristics of water seeded with chemically functionalized graphene nanoplatelets in a vertical cylindrical capsule were experimentally studied. The volume percentage of functionalized graphene nanoplatelets varied from 0.1% to 0.5% with an interval of 0.1%. The stability of the synthesized samples was measured using zeta potential analyzer. The thermal conductivity of the nanocomposite samples was experimentally measured using the transient hot wire method. A … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…However, adding nanoparticles having higher thermal conductivities as compared to base fluid could enhance the efficiency of the liquid-cooled BTMS [75]. By adding different concentrations of graphene nanoplatelets (GnP), Sidney et al [76] assessed water's thermal conductivity. They noticed that adding 0.5 vol.% of GnP enhanced the water's thermal conductivity by up to 24%.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…However, adding nanoparticles having higher thermal conductivities as compared to base fluid could enhance the efficiency of the liquid-cooled BTMS [75]. By adding different concentrations of graphene nanoplatelets (GnP), Sidney et al [76] assessed water's thermal conductivity. They noticed that adding 0.5 vol.% of GnP enhanced the water's thermal conductivity by up to 24%.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…At 4 • C HTF, f-GNP dispersion reduces nano-PCM SEC by 28%. The performance of a low-capacity energy storage tank filled with nano-PCM-containing spherical capsules was assessed by Sidney et al [19]. The findings showed that by adjusting to the HTF parameters, charging and discharging times were reduced by 18.26% to 22.8%.…”
Section: Experimental and Numericalmentioning
confidence: 99%
“…The KS1 sensor measures the thermal conductivity with an accuracy of ±5%. Thermal conductivity of the PCM nanocomposites was measured at the solid and liquid states based on the method adopted by Sidney et al [20]. Thermal conductivity measurements were performed at least 10 times at a particular temperature to confirm repeatability.…”
Section: Measurement Of Thermal Conductivity and Rheological Behaviormentioning
confidence: 99%
“…In this technique, concentrated nitric acid treatment was adopted to modify the surface of GnPs to increase the number of surface-active sites for electrochemical reactions due to the hydrophobic tendency of GnPs. The number of oxygen/nitrogen-containing functional groups formed on the surface of the graphene increased after acid treatment and thus, it increased the hydrophilicity of GnPs [20]. Moreover, studies on the rheological behavior of the PCM nanocomposites are limited in literature [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation